Preparation and Evaluation of Sustained Release Venlafaxine HCl Microspheres - Mokale, Vinod; Naik, Jitendra; Wagh, Pankaj; Khairnar, Gokul (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The aim of this study was to formulate and evaluate sustained release microsphere of Venlafaxine HCl (VF-HCl). It has many side effects with a half life around 5 hr. To reduce the adverse actions due to burst effect a sustained release (SR) Eudragit RS-100 microspheres embedded VF-HCl was formulated. The VF-HCl microspheres were prepared by oil in oil (O/O) solvent evaporation method. Drug and Polymer interaction for formulated SR Eudragit RS-100 microsphere embedded on VF-HCl was characterized by FT-IR and X-RD studie. The result showed that there is no interaction between the drug and polymer. Surface morphology of formulation carried out by FE-SEM showed good spherical geometry and uniformity in size and shape. It can be concluded that the formulated VF-HCl microspheres using widely accepted O/O method and polymer were capable for exhibiting sustained release formulation with decreasing dosing frequency thereby minimizing the occurrence of side effects with improved bioavailability. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21867 Dhaka Univ. J. Pharm. Sci. 13(1): 83-91, 2014 (June)